Konsep Husnudzan sebagai Upaya Sehat Mental pada Mahasiswa - Fitri Kamilia Azzahra (Gunung Djati Conference Series, 2023)
This study aims to discuss the concept of husnudzan as an effort to mentally healthy in students. This research is included in the type of qualitative research by applying descriptive-analytical methods. Sources of literature data related to this research topic include journals and scientific articles. The data collection technique used in this research is a literature study. The results and discussion in this study show that there is a positive correlation between husnudzan and mental health. This study concluded that husnudzan can be one of the efforts to achieve mental health in students. This qualitative research uses references from various pre-existing scientific journals which are then reviewed.